Common postoperative complication of hypertrophic pyloric stenosis - Añón, Ruben; Arruti, César; Chizzola, Manlio; Anavitarte, Eduardo (Cirugía del Uruguay, 1973)
This is a rare case of ileo-ileal invagination occurring in the immediate postoperatory period in a case of Fredet's pilororpiotomy, due to bypertropby of pilorus.